Assistance for Morning Leaf Cookies in MTs. Miftahul Hayat - Sari, Dewi Indah; Yulianti, Afni (Jurnal Menara Pengabmas, 2023)
In the food sector, food processing is growing so as to produce a variety of processed products on the market, sometimes without paying attention to the nutritional content of the food. This is one of the factors that influence people's consumption patterns, especially teenagers and children who tend to choose food that is practical, economical and quickly available for consumption. Several studies have found a high prevalence of anemia in adolescents, one of which is food consumption. Based on the results of the screening of MTs students' Hb levels. Miftahul Hayat found 43 students had anemia from 60 students who were checked for Hb and based on the results of interviews, most of the students at the school consumed food without considering the nutritional value. In general, this community service aims to help overcome the problem of anemia by utilizing existing resources around, namely by making Moringa leaf cookies. Cookies are one of the snacks that are usually favored by teenagers. Service activities begin with collecting primary data obtained from the results of Hb measurements in previous studies, then identifying problems, compiling proposals, conducting permits, socializing community service activities, mentoring participants, evaluating activities, compiling reports. This activity involved students, the head of the health center, the midwife of the health center, the principal, teachers, students and school staff. The results of the evaluation of the mentoring activity for making Moringa leaf cookies are that all participants know about anemia and the benefits of Moringa leaves and can make their own Moringa leaf cookies. The seriousness and enthusiasm of the participants and companions made this community service run according to plan. It is hoped that after this activity, these cookies can become one of the products that can have economic value that can increase school income.